KEANEKARAGAMAN TUMBUHAN PEKARANGAN DI BTN DUMAN INDAH, DESA DUMAN, KECAMATAN LINGSAR, KABUPATEN LOMBOK BARAT - Fadhila Syarifa Maulidya; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2025)
Duman is a village in Lingsar District, West Lombok Regency. The study was conducted using observational methods. Based on the study, it was found that yard plants in BTN Duman Indah, Duman Village, Lingsar District, West Lombok Regency had an H’=2.53, indicating moderate diversity, moderate distribution, and moderate community stability.